2014
DOI: 10.1080/09507116.2014.921377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the microstructure of the heat-affected zone metal in welding of high-strength steels

Abstract: To cite this article: M. Pirinen, Yu. Martikainen, S.Yu. Ivanov & V.A. Karkhin (2015) Comparative analysis of the microstructure of the heat-affected zone metal in welding of high-strength steels, Welding International, 29:4, 301-305,The welding of joints 8 mm thick in high-strength steels, produced by the quenching and tempering method and thermomechanical rolling with accelerated cooling, was investigated. It is shown that at the same strength of the steels (821 -835 MPa), the microstructure of the heat-affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…According to Kah et al [54], the welding of quenched and tempered steels is usually limited by the risk of cold cracking and the HAZ softening phenomena. The lower carbon and carbon equivalent contents permit the adoption of lower preheat temperatures to avoid cold cracking, while the HAZ softening is usually associated with microstructural changes such as the coalescence of the carbides at the subcritical region and/or the formation of upper, granular, or coalesced bainite and polygonal ferrite at the intercritical region of the HAZ are more sensitive in steels containing higher carbon contents [55]. In addition, nickel also exerts an important effect on hardenability [51,52].…”
Section: Relevant Aspectsmentioning
confidence: 99%
“…According to Kah et al [54], the welding of quenched and tempered steels is usually limited by the risk of cold cracking and the HAZ softening phenomena. The lower carbon and carbon equivalent contents permit the adoption of lower preheat temperatures to avoid cold cracking, while the HAZ softening is usually associated with microstructural changes such as the coalescence of the carbides at the subcritical region and/or the formation of upper, granular, or coalesced bainite and polygonal ferrite at the intercritical region of the HAZ are more sensitive in steels containing higher carbon contents [55]. In addition, nickel also exerts an important effect on hardenability [51,52].…”
Section: Relevant Aspectsmentioning
confidence: 99%
“…Indeed it has been shown that a quenched and tempered high strength steel compared to a thermomechanically processed high strength steel with same strengths and under similar arc welding conditions, possess different HAZ widths and microstructures [17]. Depending on the steel chemical composition, heat input in welding should be limited to a specific amount so the presence of carbides in the heat affected zone (HAZ) can be removed which increases the impact toughness of microstructure in this region [18].…”
Section: *Manuscriptmentioning
confidence: 99%
“…Welding results in the formation of material softening at the Heat Affected Zone (HAZ) which is of decisive influence on the response of the structure. Various analytical and experimental analyses have been conducted on high strength steel plates to find the governing phenomenon in the behavior of high strength material affected by welding from a metallurgical point of view [14][15][16][17][18][19]. The HAZ microstructure depends on the steel material, type of weld, heat input during welding, and the post welding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter depends mostly on the heat input, weld geometry and the thermophysical properties of the metal. The results of comparative analysis of the microstructure of the HAZ metal in welding of high-strength steels were published in [1]. The dependence of the mechanical properties on the welding conditions was studied in [2 -5], but the effect of heat input has been studied insufficiently.…”
Section: Introductionmentioning
confidence: 99%